2015
DOI: 10.1039/c5ta03425f
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic performance of long-chain poly(triphenylamine-phenothiazine) dyes with a tunable π-bridge for dye-sensitized solar cells

Abstract: A set of conjugated polymers based on poly(triphenylamine-phenothiazine) with carboxylic acid side groups have been synthesized and utilized as sensitizers for dye-sensitized solar cells (DSSCs). The polymers feature a conjugated side-chain consisting of thiophene unit (PPAT4), alternating with either a 3, 4-ethylenedioxythiophene (EDOT, PPAT5) or an EDOT-thiophene (PPAT6) as the π-bridge. This 10 methodology constitutes a consolidated step to adjust the molecular HOMO and LUMO energy levels of the dyes, hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…To achieve such ag oal, we chose triphenylamine (TPA) decorated with an azobenzene group as am onomer for the further condensation polymerization to form al ong-chain polymer structure. [11] The previous work showedt hat poly(triphenylamine) (PTPA) has ag reat potentialf or using in memory devicef abrication. [12] Due to its excellent thermal stability andalarge ON/OFFcurrent ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve such ag oal, we chose triphenylamine (TPA) decorated with an azobenzene group as am onomer for the further condensation polymerization to form al ong-chain polymer structure. [11] The previous work showedt hat poly(triphenylamine) (PTPA) has ag reat potentialf or using in memory devicef abrication. [12] Due to its excellent thermal stability andalarge ON/OFFcurrent ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we are interested in achieve a multilevel memory performance through the molecular splicing, such as a SuFEx click reaction. To achieve such a goal, we chose triphenylamine (TPA) decorated with an azobenzene group as a monomer for the further condensation polymerization to form a long‐chain polymer structure . The previous work showed that poly(triphenylamine) (PTPA) has a great potential for using in memory device fabrication .…”
Section: Introductionmentioning
confidence: 99%
“…In PTAA, substituting methyl groups at the 2‐ and 6‐positions improves its solubility. The molecular design and facile synthesis of arylamine polymers remain a topic of research …”
Section: Introductionmentioning
confidence: 99%
“…In fact, DSSCs based on sensitization of a mesoporous TiO 2 using Ruthenium polypyridyl complexes attracted considerable interest among the researchers because of their good photophysical and electrochemical properties . However, there are several detrimental factors influencing the photovoltaic performance of the cells such as light havesting efficiency, dye aggregation and electron recombination resistance . In order to address these issues, several approaches are being attempted for the development of DSSCs with improved performance.…”
Section: Introductionmentioning
confidence: 99%